Drag of generic round-shaped bodies in supersonic flow - Song, Dennis Shao Hui. (2011)
Drag has been a key research area for aerodynamicists for many years. It is the most intriguing force to compute and its reduction will bring about design breakthroughs. The objective of this study is to achieve an enhanced understanding of drag performance in supersonic flow. The various drag components were analysed over a supersonic regime between the Mach numbers 1.5 to 4 at sea level while the effects of geometry variations were investigated. The determination of drag was achieved in two different approaches, based on established theories or correlation and computational fluid dynamics. Flow properties and drag values from both sets of results were collated into an extensive database and were proven to be adequately accurate upon comparison. Results generated by these means were presented in meaningful graphs and plots for future works or reference. A detailed discussion on the trends and interesting behaviours of drag under different configurations will be included at the end of this report.